A novel precise integration-based updated numerical integration method for milling stability prediction - Liu, WeiChao; Yang, Wen-An; Chen, YuXin; You, YouPeng (International journal of advanced manufacturing technology, 2023)
Stability lobe diagrams (SLDs) can be employed to determine the stability behavior of a milling process. Hence, SLD recognition is an important issue for an effective stable machining monitoring system. Various methods have been developed for prediction of milling stability. However, the main shortcoming of such methods is that they cannot accurately and efficiently predict milling stability. This study proposes a novel precise integration-based updated numerical integration method (PI-UNIM) that can be both accurate and efficient in milling stability prediction. The fifth-order Hermite interpolation polynomial for numerical integration formula derivation is addressed in this work. Transition matrix is obtained with the precise integration algorithm. The numerical results obtained using extensive simulation indicate that the proposed method can effectively recognize SLDs for not only low immersion milling situation but also high immersion milling situation. Empirical comparisons show that the proposed method performs better than existing methods in terms of computation accuracy and computation efficiency. A demonstrative example is provided to illustrate the usage of the proposed method.